Towards the standardization of Enterococcus culture methods for waterborne antibiotic resistance monitoring: A critical review of trends across studies. (1st December 2022) - Davis, Benjamin C.; Keenum, Ishi; Calarco, Jeannette; Liguori, Krista; Milligan, Erin; Pruden, Amy; Harwood, Valerie J.
Highlights: Enterococcus = Gram-positive candidate for antimicrobial resistance surveillance. Culture provides valuable data on viability, phenotype, and multidrug resistance. Modern standard methods improve specificity and allow comparisons among studies. Confirmation of the genus is essential for meaningful data. Flowchart recommends workflow based on monitoring objectives. Abstract: Antibiotic resistance is a major 21 st century One Health (humans, animals, environment) challenge whose spread limits options to treat bacterial infections. There is growing interest in monitoring water environments, including surface water and wastewater, which have been identified as key recipients, pathways, and sources of antibiotic resistant bacteria (ARB). Aquatic environments also facilitate the transmission and amplification of ARB. Enterococcus spp. often carry clinically-important antibiotic resistance genes and are of interest as environmental monitoring targets. Enterococcus spp. are Gram-positive bacteria that are typically of fecal origin; however, they are also found in relevant environmental niches, with various species and strains that are opportunistic human pathogens. Although the value of environmental monitoring of antibiotic-resistant Enterococcus has been recognized by both national and international organizations, lack of procedural standardization has hindered generation of comparable data needed to implement integrated surveillance programs. Here we provide a comprehensive methodological review to assess the techniques used for the culturing and characterization of antibiotic-resistant Enterococcus across water matrices for the purpose of environmental monitoring. We analyzed 117 peer-reviewed articles from 33 countries across six continents. The goal of this review is to provide a critical analysis of (i) the various methods applied globally for isolation, confirmation, and speciation of Enterococcus isolates, (ii) the different methods for profiling antibiotic resistance among enterococci, and (iii) the current prevalence of resistance to clinically-relevant antibiotics among Enterococcus spp. isolated from various environments. Finally, we provide advice regarding a path forward for standardizing culturing of Enterococcus spp. for the purpose of antibiotic resistance monitoring in wastewater and wastewater-influenced waters within a global surveillance framework. Graphical abstract: Image, graphical abstract